GAMBARAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN KUNJUNGAN K1 DI WILAYAH PUSKESMAS PELAMBUAN KECAMATAN BANJARMASIN BARAT TAHUN 2017 - Dian Purnama Sari (Journal of Midwifery and Reproduction, 2018)
Background:Based onsecondary datawhichare expected totargetpregnant womeninthe Work AreaHealth CenterPelambuanIn the Year2017is equal to826 people, ofpureK1visitofthe monthJanuary to Aprilreachedby 188people(22.8%). This suggeststhat the scope ofK1inthe Work AreaHealth Centeris still notbeing metPelambuanofthe expected target. Objectives: Toknow the description ofthe knowledgeandattitudesof pregnant womenabout the visitinthe Work AreaK1PelambuanHealth Centerin 2017. MaterialandMethod: The study used apurposivesamplingwith a sample ofthe study wereallpregnant womenareworkingin the regionPelambuanHealth Centerin 2017, amounting to 65 people. Conclusion: From these results, of the65motherswho visitedK1Pure13 people(20%) andK1Access52 people(80%). Pregnant women who arebothknowledgeable27 people(41.53%), just 26 people(40%), less well8 people(12.30%). Pregnant womenarebeingeither22 people(33.84%), just 38 people(58.46%) and pregnant womento beless well5(7.69%). In this studyit is advisable forhealth workerstofurther enhanceeducation aboutK1visitsfor pregnant womenespeciallybenefitfromthevisit ofK1, andfor pregnant womenexpected to bemore activeinasking questions andrequestinginformation tohealth workersso as toknow and understandabout thevisit of K1.